Comparison of different orders padé fractional order PD0.5 control algorithm implementations - Silva, Manuel (2019)
This paper studies the performance of different order Padé Fractional Order (FO) PD0.5 controllers applied to the leg joint control of a hexapod robot with two dof legs and joint actuators with saturation. For simulation purposes the robot prescribed motion is characterized through several locomotion variables and for the walking performance evaluation are used two indices, one based on the mean absolute density of energy per travelled distance and the other on the hip trajectory errors. A set of simulation experiments reveals the influence of the different order Padé PD0.5 controllers tuning upon the proposed indices.